2009
DOI: 10.1063/1.3216373
|View full text |Cite
|
Sign up to set email alerts
|

Geometric bonding effects in the X A21, A Σ2u+, and B Π2g states of Li2F

Abstract: Published ab initio and pseudopotential calculations for the dialkali halide systems suggest that the preferred colinear geometry is for the metal to approach the metal end of the alkali halide. Here, ab initio calculations on the Li 2 F system reveal that the well depth on the halide side in this radical is much deeper and is a local saddle point associated with the ionic nonlinear global minima. Although many features of the pseudopotential surfaces are confirmed, significant differences are apparent includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…17 Furthermore, some investigations have shown that central atoms in such species need not be a metal These molecular species possess potential reducing capability and can be used in the synthesis of a variety of charge transfer salts. Li 2 F has been extensively studied theoretically 2,[22][23][24][25][26] as well as experimentally. [27][28][29] Like alkali metal cations, superalkali cations may interact with superhalogen anions and this interaction can be expected to be stronger than the former due to even lower IPs of superalkalies.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, some investigations have shown that central atoms in such species need not be a metal These molecular species possess potential reducing capability and can be used in the synthesis of a variety of charge transfer salts. Li 2 F has been extensively studied theoretically 2,[22][23][24][25][26] as well as experimentally. [27][28][29] Like alkali metal cations, superalkali cations may interact with superhalogen anions and this interaction can be expected to be stronger than the former due to even lower IPs of superalkalies.…”
Section: Introductionmentioning
confidence: 99%
“…The standard formula for superalkalis is M k+1 L, where k is 1 for L (F, Cl, Br, and I) and 2 for L (O) atoms; Li n X ( Velickovic et al, 2006 ; Velickovic et al, 2007 ; Velickovic et al, 2012 ) extended to K 2 X (X = F, Cl, Br, and I) ( Velickovic et al, 2011 ) and Li 3 O ( Zintl and Morawietz, 1938 ; Kudo et al, 1978 ; Wu et al, 1979 ) are two instances that come up frequently in this series. Li 2 F has been the subject of extensive theoretical ( Gutsev and Boldyrev, 1982 ; Honea et al, 1989 , Honea et al, 1993 ; Rehm et al, 1992 ; Koput, 2008 ; Wright et al, 2009 ) and experimental ( Yokoyama et al, 2000 ; Neskovic et al, 2003 ; Fernandez-Lima et al, 2009 ) research. Well-known superalkalis, M 3 O (M = Li, Na, and K), have a greater propensity than their equivalent alkali atoms to lose an outer electron ( Gutsev and Boldyrev, 1987 ; Rehm et al, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…The global energy minimum [33] occurs for the perpendicular reaction geometry, which is indicative of a charge transfer system. Furthermore, this is true for the lowest two excited 2 A states (a three-state calculation includes the 2 A component of the B 2 state).…”
Section: Entrance-channel Electronic Statesmentioning
confidence: 99%